PERAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DALAM PENINGKATAN KINERJA INDIVIDU DI SEKTOR PUBLIK: SEBUAH ANALISIS TEORITIS DAN EMPIRIS (THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN THE INDIVIDUAL PERFORMANCE IMPROVEMENT IN THE PUBLIC SECTOR - Mariman Darto (Pusjar SKPP Lembaga Administrasi Negara, 2014)
This study aims to analyze the role of Organizational Citizenship Behavior (OCB) in improving individual performance in the public sector from the theoretical and empirical perspective. Data were gathered through a stock- taking technique by collecting and classifying various textbooks and journals as well as a variety of relevant previous studies. This study finds that OCB has a vital role in the individual performance improvement in the public sector. OCB significantly related to individual performance. However, further studies are required to see how significance the relationship between OCB and individual performance in government organizations. Keywords: organizational citizenship behavior, individual performance, organizational behavior.Kajian ini bertujuan untuk menganalisis peran Organizational Citizenship Behavior (OCB) dalam peningkatan kinerja individu di sektor publik, dilihat dari perspektif teoritis dan empiris. Pengumpulan data dilakukan melalui teknik stock taking dengan cara mengumpulkan dan mengklasifikasi berbagai textbook dan jurnal serta berbagai penelitian terdahulu yang relevan. Kajian ini menemukan bahwa OCB memiliki peran vital dalam meningkatkan kinerja individu di sektor publik. OCB berhubungan secara signifikan terhadap kinerja individu. Meskipun demikian diperlukan berbagai kajian lanjutan yang mendalam untuk melihat signifikansi hubungan OCB dengan kinerja individu pada organisasi pemerintah. Kata Kunci : organizational citizenship behavior, kinerja individu, perilaku organisasi